Cannabis Use, Problem-Gambling Severity, and Psychiatric Disorders: Data from the National Epidemiological Survey on Alcohol and Related Conditions - Hammond, Christopher J. (Psychol Addict Behav, 2019)
Cannabis use and related disorders are common in adults and frequently co-occur with subsyndromal and pathological gambling. However, understanding how cannabis use may moderate relationships between problem-gambling severity and psychiatric disorders remains poorly understood. Data from the National Epidemiological Survey on Alcohol and Related Conditions (N=43,093 adults) were examined to investigate how cannabis use moderated associations between problem-gambling severity (with gambling groups based on the 10 DSM-IV inclusionary criteria for pathological gambling) and Axis I and Axis II psychiatric disorders. Problem-gambling severity groups included low frequency/non-gambling (LFG/NG), low-risk gambling (LRG), at-risk gambling (ARG), and problem/pathological gambling (PPG). Among both the group with lifetime cannabis use and that which never used cannabis, greater problem-gambling severity was associated with more psychopathology across mood, anxiety, substance-use and Axis II disorders. Significant cannabis-use-by-problem-gambling-severity-group interactions were observed between PPG and major depression (OR=0.35, 95%CI=[0.14–0.85]), cluster A personality disorders (OR=0.37, 95%CI=[0.16–0.86]) - especially paranoid personality disorder (OR=0.34, 95%CI=[0.14–0.81]), and cluster B personality disorders (OR=0.36, 95%CI=[0.18–0.75]) - especially antisocial personality disorder (OR=0.25, 95%CI=[0.11–0.60]). In all cases, associations between problem-gambling severity and psychopathologies were weaker among the lifetime-cannabis-using group as compared to the never-using group.. Cannabis use moderates the relationships between problem-gambling severity and psychiatric disorders, with cannabis use appearing to account for some of the variance in the associations between greater problem-gambling severity and specific forms of psychopathology.